2020
DOI: 10.3389/fimmu.2020.02156
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Receptors and Checkpoints in Human NK Cells, Implications for the Immunotherapy of Cancer

Abstract: The highly destructive mechanisms by which the immune system faces microbial infections is under the control of a series of inhibitory receptors. While most of these receptors prevent unwanted/excessive responses of individual effector cells, others play a more general role in immunity, acting as true inhibitory checkpoints controlling both innate and adaptive immunity. Regarding human NK cells, their function is finely regulated by HLA-class I-specific inhibitory receptors which allow discrimination between H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 129 publications
0
57
0
Order By: Relevance
“…NC410 may also have additional LAIR-1-independent mechanisms of action since we have previously shown that LAIR-2 Fc can efficiently inhibit complement activation via classical and lectin pathways ( Olde Nordkamp et al, 2014a ). Therefore, we cannot exclude that NC410 blocks other receptors or impacts other cells than T cells ( Sivori et al, 2020 ) or has additional functions besides outcompeting LAIR-1. These functions of NC410 will be examined as part of ongoing clinical trials, as well as with additional preclinical models.…”
Section: Discussionmentioning
confidence: 99%
“…NC410 may also have additional LAIR-1-independent mechanisms of action since we have previously shown that LAIR-2 Fc can efficiently inhibit complement activation via classical and lectin pathways ( Olde Nordkamp et al, 2014a ). Therefore, we cannot exclude that NC410 blocks other receptors or impacts other cells than T cells ( Sivori et al, 2020 ) or has additional functions besides outcompeting LAIR-1. These functions of NC410 will be examined as part of ongoing clinical trials, as well as with additional preclinical models.…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acids, extracellular matrix/collagen or aminophospholipids was expressed on the surface of tumor respectively, which could be recognized by sialic acids, extracellular matrix/collagen or aminophospholipids expressed on the surface of NK cells. Thus, NK cell function was inhibited (48).…”
Section: Tumor-infiltrated Nk Cells Exhibit An Altered Phenotypementioning
confidence: 99%
“…Tyrosine phosphorylation of ITIMs allows the recruitment of protein tyrosine phosphatases SHP-1 and SHP-2, leading to the transmission of inhibitory signals that limit the strength of signals received from activating receptors [ 27 ]. Classical NK cell inhibitory receptors bind to MHC molecules called HLA in humans [ 28 ]. Through these interactions, inhibitory NK cell receptors are responsible for the “missing-self recognition”, a process whereby NK cells recognize foreign or dangerous autologous cells that might have escaped adaptive immunity through down-regulation of surface class I MHC (MHC-I) molecule expression [ 29 ].…”
Section: Inhibitory Receptors Binding To Mhc-i Moleculesmentioning
confidence: 99%